ANALYSING THE EFL UNDERGRADUATE STUDENTS’ PLAGIARISM IN WRITING ACADEMIC PAPERS - Nugraha, Ramdan; Putra, Juang Rudianto (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2018)
This research is aimed to identify the forms of plagiarism and to reveal the factors contribute toward the emergence of plagiarism in students’ undergraduate research papers. The method used is qualitative approach using content analysis. The data collection was done through analysing documents (respondents’ papers) and interviewing the respondents and the lecturers of a private college in Bogor. The research found that there are three kinds of plagiarism forms produced by the undergraduate students; 1) Totally Copy-Paste (TCP) which means copying the texts as the same as the original without crediting the authors; 2) Totally Copy-Paste from the Mentioned Author (TCP-MA) means the respondents once credited the name of the author, but then they copied the original texts and pasted them as many pages as they needed without paraphrasing at all; and 3) Copy-Paste and Deleting and/or Changing Few of Original Words (CP- DCFOW) which is almost the same as TCP but few words were deleted or changed from the original sources without crediting the authors. In addition, the factors contributed toward the emergence of plagiarism were the respondents’ idleness to understand the academic paper procedure, the respondents’ pragmatic views during conducting their academic paper, the respondents’ low confidence to write their own ideas on their academic paper, and the respondents’ skill to adress their ideas into the context of English academic paper.